El papel de las dietas altas en proteínas y la actividad física en la pérdida de grasa y la salud metabólica: Implicaciones para sistemas alimentarios sostenibles - Zadgaonkar, Umesh (Retos, 2025)
Introduction: Obesity and related metabolic disorders, including type 2 diabetes and cardiovascular diseases, are increasing globally, making effective interventions crucial. High-protein diets and structured physical activity are promising strategies to combat these issues.Objective: This study aims to evaluate the impact of high-protein diets combined with physical activity on fat loss, metabolic health, and the sustainability of food systems.Methodology: A 12-week randomized controlled trial involving 60 participants assessed the effects of a high-protein diet (1.6-2.0 g/kg body weight) and structured physical activity (aerobic and resistance training) on body composition, glucose metabolism, and lipid profiles. The control group followed a balanced diet without exercise intervention. Data on anthropometry, biochemical markers, and adherence to protocols were collected.Results: The intervention group showed significant reductions in body weight (6.2 kg), fat mass (4.8 kg), and waist circumference (8.5 cm). Fasting glucose levels and lipid profiles improved, with a 12% reduction in glucose and an 18% reduction in LDL cholesterol. The control group exhibited minimal changes.Discussion: The combined intervention of high-protein diets and physical activity demonstrated synergistic effects on fat loss and metabolic health, highlighting the importance of integrated strategies for obesity management. gender-specific responses were also observed.Conclusions: This study supported the efficacy of combined dietary and exercise interventions in promoting fat loss and improving metabolic health. However, further long-term studies are needed to evaluate sustainability and broader applications for public health.